Proceedings of the 13th International Conference on Global Software Engineering 2018
DOI: 10.1145/3196369.3196375
|View full text |Cite
|
Sign up to set email alerts
|

Employee retention and turnover in global software development

Abstract: Poor employee retention (high staff turnover) has a negative impact on software development productivity and product quality. Further, offshore outsourcing has a widely held reputation for particularly poor employee retention. Interestingly, in-house sites (regardless of location) do not suffer such high levels of staff turnover.We want to understand the factors affecting employee retention in-house and offshore outsourced settings, to better understand the potential impact of staff turnover on global software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…The same researcher also indicates that some of the risks confronted by a software development project are cultural and linguistic differences, motivation, and temporal distance 77 and that these affect aspects as important as coordination, the visibility of the project, cooperation, and communication. In their work, Šmite and Wohlin 78 stated that transferring software development work to locations that are geographically, temporally, and culturally distant negatively influences performance, while Bass et al 79 analyzed the aspects that have an influence on software developers' motivation and found that things such as bad company policies, an excess of extra working hours, having to work antisocial hours and temporal distance may have a negative effect on employees' motivation. Furthermore, Amin et al (2011) focused on analyzing the aspects that cause work‐related stress in software engineering professionals and discovered that pressure to update knowledge, lack of confidence, cultural, or linguistic differences or temporal distance, among others, have a negative effect on professionals' levels of stress.…”
Section: Results: Stress Motivation and Performance In Gsdmentioning
confidence: 99%
“…The same researcher also indicates that some of the risks confronted by a software development project are cultural and linguistic differences, motivation, and temporal distance 77 and that these affect aspects as important as coordination, the visibility of the project, cooperation, and communication. In their work, Šmite and Wohlin 78 stated that transferring software development work to locations that are geographically, temporally, and culturally distant negatively influences performance, while Bass et al 79 analyzed the aspects that have an influence on software developers' motivation and found that things such as bad company policies, an excess of extra working hours, having to work antisocial hours and temporal distance may have a negative effect on employees' motivation. Furthermore, Amin et al (2011) focused on analyzing the aspects that cause work‐related stress in software engineering professionals and discovered that pressure to update knowledge, lack of confidence, cultural, or linguistic differences or temporal distance, among others, have a negative effect on professionals' levels of stress.…”
Section: Results: Stress Motivation and Performance In Gsdmentioning
confidence: 99%
“…La gestión del personal, es decir, elementos como la rotación de personal (Bass et al, 2018;Dingsoyr et al, 2016) tanto interna (como se mencionó en la dimensión de equipos) como externa, normalmente es percibida como una influencia negativa y el staffing (Alahyari et al, 2018) se torna una actividad relevante.…”
Section: El Detalle Del Análisis Completounclassified
“…As previously discussed, communication, coordination, and control are essential components in RCM and implementation process, especially when outsourcing a software product [32]- [34]. Thus, it is of vital importance to select the most viable methods, tools, and technology to effectively implement the RCM process in GSD [26]- [28], [35], [36].…”
Section: Research Motivationmentioning
confidence: 99%